Complex evolution of mitochondrial genomes: lessons from salamanders - Chong, Rebecca A., author; Mueller, Rachel L., advisor; Webb, Colleen T., committee member; Funk, W. Chris, committee member; McKay, John K., committee member (Colorado State University. Libraries, 2014)
This dissertation research on genome evolution focuses on understanding the mechanisms that drive the evolution of mitochondrial genome size, content, and organization in animals. This research uses a combination of empirical and computational approaches to examine the evolution of mitochondrial genomes in vertebrates, focusing on salamanders as an exemplar clade. Chapter One analyzes mitochondrial genome sequences of vertebrate lineages that differ in metabolic rates. Salamanders, which have the lowest metabolic requirements among tetrapods, experience weaker purifying selection on protein-coding sequences than do frogs, a comparable amphibian clade with higher metabolic rates. In contrast, there is no evidence for weaker selection against mitochondrial genome expansion in salamanders. Together, these results suggest that different aspects of mitochondrial genome evolution (i.e. nucleotide substitution, accumulation of non-coding sequences) are differently affected by metabolic variation across tetrapod lineages. Chapter Two describes the correlation between gene rearrangement/genome expansion and increased rates of substitution in salamander mitochondrial genomes. Most protein-coding genes maintain their position along the mutation gradient in rearranged/expanded mitochondrial genomes, and the genes that do move are unaffected by their new position because the mutation gradient in salamanders is weak. Additionally, genomic rearrangements/expansions occur independent of levels of selective constraint on genes. Together, these results demonstrate that large-scale changes to genome architecture impact mitochondrial gene evolution in predictable ways; however, despite these impacts, the same functional constraints act on mitochondrial protein-coding genes in both modified and normal genomes. Chapter Three reports the phylogenetic relationships among lineages of Aneides, sampling both within and among all six species, based on three nuclear markers and describes mitochondrial genome sequences for nine of the taxa represented in the phylogeny. Mitochondrial gene order and level of mitochondrial sequence divergence were estimated for these sequences and two previously published sequences. Two genome duplication events resulting in mitochondrial gene rearrangements were detected, the first rearrangement occurring in the common ancestor of Aneides and the second rearrangement existing across different populations of a single species, A. hardii. Comparisons of A. hardii genomes show that duplicated protein-coding and rRNA genes are lost more rapidly than other duplicated mitochondrial sequence (i.e. tRNAs, non-coding sequence) and suggests that these large scale changes can occur across very shallow levels of genetic divergence.
Keywords: gene duplication; molecular evolution; mutation; natural selection; genomics